Ochrona interesów konsumentów przed działaniami parabanków sprawowana przez Urząd Ochrony Konkurencji i Konsumentów - Majewska-Jurczyk, Barbara (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The article presents the problem of the functioning of parabanks in Poland and the role of the Office of Competition and Consumer Protection in consumer protection from parabanks unfair practicies on financial services market. The aim of the Office of Competition and Consumer Protection is the observation and prohibition of parabanks activities which are connected with high costs of loans and credits for consumers. Activities of parabanks are connected with the economic risk for consumers
Keywords: rynek finansowy; ochrona konsumentów; parabanki; nieuczciwa reklama; wzorce umów